Work-Family Policies and Gender Inequalities in Childcare Time. (December 2022) - Gao, Melody Ge; Ruan, Hangqing
Work-family policies are promoted to reduce gender inequalities in childcare time. However, the association between work-family policies and childcare time is complicated by the conditions of the policies and how mothers and fathers perform childcare. The authors examine whether three widely discussed work-family policies—paid parental leave, flextime, and flexplace—are associated with reduced gender differences in two dimensions of childcare time: solo versus shared care with a partner and basic versus developmental childcare activities. Using 2017–2018 Leave and Job Flexibilities Module of the American Time Use Survey, this study indicates that gender inequalities in childcare time decrease among parents who have access to paid parental leave or frequently use the flexplace policy, which provide both available time and direct exposure to childcare tasks. Policies with these characteristics also help close gender gaps in solo and basic childcare time that are vital in shaping gender inequalities in society.